Evaluation of water oxygenation onmilk production: milk composition andsomatic cell concentration in milk - John E. Shirley; C. Galdamez; J. Estrada (Kansas Agricultural Experiment Station Research Reports, 1989)
Forty Holstein cows in mid-lactation were utilized to evaluate the effects of water oxygenation on milk production, milk composition, and somatic cell count. Cows were fed a total mixed ration consisting of 25% alfalfa, 25% corn silage, and 50% corn-soy concentrate on a dry matter basis. Treatments included a 7-day preliminary period followed by two 28-day periods in which the treatments were reversed. Water consumption, milk production, milk composition, and somatic cell count were not different between treatments. Cows receiving oxygenated water were more docile and easily managed than control cows. Ozone introduced into water forms hydrogen peroxide, nitrous oxide, and increases the redox potential of the water.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Water oxygenation; Milk production; Somatic cell concentration